Expanding the Role of Heparin Derivatives in Oncology: From Anticoagulation to Antitumor Activity - Jasmine Holail; Hatouf Husni Sukkarieh; Ahmad Aljada (Pharmaceuticals)
Current research demonstrates the expanding therapeutic potential of heparin derivatives in oncology, extending beyond traditional anticoagulation mechanisms. This systematic analysis examines the structural characteristics, molecular mechanisms, and therapeutic applications of heparin-based compounds in malignancy treatment. The essential antithrombin binding pentasaccharide sequence has enabled development of specialized molecular variants, particularly fractionated heparins and their non-anticoagulant counterparts. These agents exert antineoplastic effects via multiple pathways, particularly through modulation of heparanase enzymatic activity and specific protein–glycosaminoglycan interactions. Evidence from pivotal clinical trials (FRAGMATIC, MAGNOLIA, GASTRANOX) confirms efficacy in managing cancer-associated thrombosis while indicating potential enhancement of chemotherapeutic outcomes. The preparation methods utilize enzymatic cleavage reactions and selective chemical derivatization to generate structurally modified heparins exhibiting unique molecular characteristics and biological activities. Analysis of the glycosaminoglycan analog dociparstat sodium reveals significant activity in myeloid malignancies, mediated by specific interference with CXCL12/CXCR4 signaling cascades. Significant challenges remain in manufacturing scale-up, analytical validation, and long-term safety assessment. Future studies must address dose optimization, combination strategies, and controlled clinical trials to determine the full therapeutic potential of these compounds in clinical oncology.